Clinicopathological analysis and survival outcome of duodenal adenocarcinoma. Issue 5 (17th January 2014) - Kim, Myung Jin; Choi, Sae Byeol; Han, Hyung Joon; Park, Pyoung Jae; Kim, Wan Bae; Song, Tae Jin; Suh, Sung Ock; Choi, Sang Yong
Abstract: Duodenal adenocarcinoma is a rare cancer, contributing <10 % of periampullary carcinoma. This study reviews the single center experience of duodenal adenocarcinoma and analyzes the clinical and pathological factors to predict survival and recurrence. The records of 50 patients with duodenal adenocarcinoma who underwent surgical exploration or resection from 1995 to 2010 were reviewed retrospectively. Univariate and multivariate analyses were performed to identify the clinicopathological factors associated with survival and recurrence. There were 35 men and 15 women, with a mean age of 61 years. In multivariate analysis of 50 patients, R0 resection [ p  = 0.041, hazard ratio (HR) = 3.569, 95% confidence interval (CI) = 1.057–12.054] and symptom at initial admission ( p  = 0.025, HR = 11.210, 95% CI = 1.354–92.812) were independent prognostic factors for overall survival. Thirty‐six patients underwent curative resection (resectability 72%). The 5‐year survival rates for curative and noncurative resections were 46.4% and 0%, respectively. Univariate analysis of 36 patients who underwent R0 resection revealed that symptoms at initial admission ( p  = 0.023), presence of lymph node metastasis ( p  = 0.034), and perineural invasion ( p  = 0.025) were significant prognostic factors after curative resection. There was no significant factor for overall survival in the multivariate analysis. There was recurrence in 15 patients, mainly as liver metastasis. Multivariate analysis revealed that presence of symptom ( p  = 0.047, HR = 5.362, 95% CI = 1.021–28.149) and ulcerative tumor ( p  = 0.036, HR = 5.668, 95% CI = 1.123–28.619) were independent factors for disease free survival. An aggressive surgical approach to achieve R0 resection was important to enhance survival. Most of the recurrence occurred within 1 year after surgery. Close follow‐up is necessary after surgical resection.